Water-soluble Fraction of Abelmoschus esculentus L Interacts with Glucose and Metformin Hydrochloride and Alters Their Absorption Kinetics after Coadministration in Rats. (11th September 2011) - Khatun, Hajera; Rahman, Ajijur; Biswas, Mohitosh; Islam, Anwar Ul
Abstract : This study was done to investigate the effects of water-soluble fraction (WSF) of the fruits of Abelmoschus esculentus L (okra/lady's fingers) on absorption of oral glucose as well as metformin from the gastrointestinal tract in the Long Evans rats. WSF of A. esculentus significantly (P < 0.05 ) reduced the absorption of glucose as studied in the 24 hrs fasting rats. The effect of WSF of A. esculentus on metformin absorption was studied in alloxan-induced diabetic rats. Significant differences (P < 0.05 ) were observed in the average blood glucose level from 2 to 24 hours after metformin therapy in presence (33.6 to 34.2 mmol/L) or absence (15.2 to 20.2 mmol/L) of oral WSF of A. esculentus . In both of the experiments, Na-carboxymethylcellulose (CMC) was used as positive control. The results of this study indicate that A. esculentus may improve glycemic control but should not be taken concurrently with metformin hydrochloride in controlling diabetes mellitus.